Evaluation of the agriculture land contamination with heavy elements in sumer city - AL-Awasy, Wafaa Sahib Abbod; AL-Kinany, Fadhel S .; Al - Abudi, Luma Abdalalah Sagban; Noori, Noor Ahmed (Journal of Kerbala for Agricultural Sciences, 2018)
The reality of the pollution of cadmium, lead and nickel was studied in four agricultural sites and for different distances. The first site is about 7 meter away from the main road leading to the city of Sumar - Diwaniyah governorate. The second location is about 100 meters away from the main street.. The third site is about 200 meters away and the fourth site is about 300 meters And for two different depths (0-15 cm) and (15-45) cm. Soil samples were analyzed to estimate concentrations of the above-mentioned heavy metals for both soil and plants. The results showed that the concentration of cadmium, lead and nickel in the soil samples of the study and when compared with the determinants of the World Health Organization (WHO) showed that it did not exceed the permissible limit, with a concentration rate of ( 0.032- 0.142 ) mg Kg-1 and (0.680 - 1.580) mg Kg-1 and (8.750 - 14.200) mg Kg-1 respectively, The highest concentration was recorded at the first site near the source of pollution (the main street leading to the city of Sumer) and the lowest concentration at the last site, which is 300 meters from the main street. The results also showed that the surface of the soil is more susceptible to pollution than other layers. When compared the laboratory results of concentrations of heavy metals studied in plant models with WHO determinants, the lead component showed a clear increase in the study models from the WHO limit of 0.3 mg Kg-1, with the highest concentration at 1.70 mg Kg-1 - With the knowledge that the concentration in the soil of the study did not exceed the permissible limit, which indicates the high susceptibility to the absorption of plants for this element, albeit with a few concentrations and this indicates the seriousness of plant cultivation in soil contaminated with this element.